Birthweight ratio revisited. Issue 4 (April 1991) - Brownlee, K G; Ng, P C; Roussounis, S H; Dear, P R
Abstract : In order to test the hypothesis suggested in a recent report that the birthweight ratio might be a useful predictor of several important clinical outcome measures in babies of less than 31 weeks' gestation, we examined the association between the birthweight ratio and aspects of both short and long term outcome in 436 Leeds babies of less than 31 weeks' gestation. Unlike the report, and contrary to what we had expected, we were unable to find any significant association between birthweight ratio and length of time on the ventilator, mortality, neurological outcome, or intellectual outcome.